Pengaruh Kapasitas Working Memory dan Kemampuan Numerik terhadap Pemecahan Masalah Matematika Berbasis Higher Order Thinking Skills - Azin Taufik; Ria Rahmadayanti; Rahayu Syafari (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
This research is motivated by the low ability of solving mathematical problems based on Higher Order Thinking Skills (HOTS) in junior high school students. The objectives of the study are to: analyze the effect of working memory capacity on HOTS-based mathematical problem solving, analyze the effect of numerical ability on HOTS-based mathematical problem solving, and analyze the effect of working memory capacity and numerical ability simultaneously on HOTS-based mathematical problem solving. This type of research is quantitative with a causal associative research design. The research was conducted at SMP Negeri 1 Kalimanggis. Data collection techniques used test questions and interviews. The instruments used include: Operation Span (OSPAN) task, numerical ability test and HOTS-based mathematical problemsolving test. Data analysis techniques used simple and multiple linear regression with the help of Excel software. The results of the study showed that: Working memory capacity has a positive and significant effect on HOTS-based problem solving , ), numerical ability has a positive and significant effect on HOTS-based problem solving ( , ), and both factors simultaneously have a positive and significant effect ( , ).